Potential effect of tropospheric polar vortex and large-scale atmospheric circulation on extreme winter temperature over Iraq (1–15 February 2020 case study) - Muslih, Khamis; Abbas, Ahmad Majid (Bulletin of Geography. Physical Geography Series, 2025)
The Middle East region is characterized by rapidly changing temperatures that could have a direct and severe impact on human beings. During the period 1st–15th February 2020, the weather in Iraq was characterized by extreme heat and cold temperature spells. This paper investigates the role of polar vortex and large-scale atmospheric circulation in the occurrence of these events. The data used are daily minimum temperatures for 12 meteorological stations, daily data of the Arctic Oscillation Index (AOI) and North Atlantic Oscillation Index (NAOI), and reanalysis data. Our results show that extreme daily temperatures were overly sensitive and responsive to variability in the magnitude and strength of the polar vortex. Teleconnection analysis revealed that the rapid variations of polar vortex that manifested as significant changes in the NAO–AO indexes were accompanied by strong meridional circulation activity within 45° to 70° N, which enhanced the chance of occurrence of extreme temperature events.